INVESTIGATING CAUSES OF GRAMMATICAL ERRORSIN WRITING NARRATIVE TEXT AT ELEVENTH GRADE OF SMA NEGERI 1 SIANTAN - Permatasari, Sherly; Anita, Finny; Syahadati, Elly; Ayu Tira, Marsa (Journal of English Language Teaching and Education (JELTE), 2024)
Grammatical errors in writing narrative texts in English are quite diverse and often occur in new or experienced writers. The purpose of this study was to analyze grammatical errors in writing narrative texts and find the main causes of eleventh grade students at SMA Negeri 1 Siantan often making grammatical errors when writing narrative texts. Many students often experience grammatical errors in their writing that can interfere with students' ability to write effectively. This study analyzed error data from narrative texts made by 28 students using a qualitative descriptive approach with a method of analyzing student assignments in writing narrative texts to collect data to see the location of grammatical errors that are often made when writing, then a number of students were interviewed to investigate the causes of the errors. the results of this study indicate that students when writing narrative texts make many errors in omission and the cause is because students often write narrative texts in English always write in the first language that is translated into English, this is what causes differences in the grammar of the translation and causes students to make grammatical errors in writing narrative texts. Keywords: Grammatical errors, error analysis, writing narrative texts.